An Overview of Corporate Governance Practices of Selected Islamic Banks - Zainab Belal; Mustapha Hamat (Universitas Darussalam Gontor, 2016)
Complying with Corporate Governance (CG) standards is not mandatory but with collapse of many financial institutions, compliance with high standards of CG in banking operation has become a necessity. This is due to the fact that many banks and companies worldwide collapsed as a result of poor corporate governance practices such as Bank of Credit and Commerce International (BCCI) 1991, Barings Bank 1995, Lehman Brothers 2008, Enron 2001, WorldCom 2001, etc. Therefore, the objective of this paper is to examine and ascertain whether present level of CG standards practiced by Islamic banks is adequate to prevent or safeguard the banks from collapsing. The approach of the study is to evaluate the effectiveness of board and the various board committees utilizing data published in financial statement of the selected banks. The methodology used in this paper is analytical descriptive to reach accurate results and as more appropriate approach with this research. The study finds out that the selected banks comply with CG standards adopted; however such compliance does not mean that the board, the board committees will be constantly reliable. Therefore, instilling the Islamic values such as the concepts of iḥsân, honesty, and accountability is paramount to prevent CG failures and protect/safeguard the banks from collapsing.